The significance of heritage trees conservation for urban development in Taiping Lake Garden, Malaysia - Mohd Ariffin, Noor Fazamimah; Abdul Aziz, Noor Azramalina; Mohd Yunos, Mohd Yazid (Universiti Putra Malaysia Press, 2019)
Lack of awareness on the environmental benefits and services offered by urban heritage trees among the decision makers and society has endangered these urban heritage trees, thus they are not recognized as an important asset. Heritage trees are important in giving historical identity and cultural symbolic to the landscape of the cities. Rapid development of urban areas in Malaysia has changed the land use of natural environment to into built environment. This situation causes a lot of urban heritage trees to be felled to make way for urban development. The main objective of this paper is to identify and analyze the benefits of heritage trees in Taiping Lake Garden based on tourists respond. This research has applied a contingent valuation survey questionnaire in collecting the data. A total of 400 tourists were randomly interviewed in Taiping Lake Garden. The study was also focused on the importance of preserving the non-use value and inducing public awareness on conservation of heritage trees as part of landscape roles to create culture and historical value in cities. Analyzing benefits of heritage tree through a participatory process that involves the tourists could help to promote the sustainability of the Urban Heritage Trees conservation efforts in Taiping Lake Garden.